Influence of climatic conditions on nutritional and nutraceutical profiles of organic-grown sweet red-peppers (Capsicum annuum L.) - Di Cesare, Luigi Francesco; Migliori, Carmela Anna; Leteo, Fabrizio; Campanelli, Gabriele (Progress in Nutrition, 2014)
This research showed the evaluation of some quality parameters in two red-pepper genotypes named “Alceste” and “RS08” cultivated with organic system in two seasons, on 2010 and 2011, in 11 years organic-converted soils. All samples, harvested at commercial ripening, have been subjected to some quality aspects as follows. Nutritional quality: soluble sugars, pyrazine volatile compounds. Nutraceutical quality: ascorbic acid, polyphenols, carotenoids and antiradical capacity. The attention was particularly focused on pyrazines (2-methoxy-3-isopropyl pyrazine and 2-methoxy-3-isobutyl pyrazine), for their interesting odorous properties. Moreover, the antioxidant profile (mainly ascorbic acid and carotenoids) was examined for its role in the nitrosamine inhibition, that is responsible of some tumors. The main finding was a clear difference in both genotypes in the behavior of phytochemicals: pyrazine increased in 2011 with respect to 2010, while sugars and the nutraceutical profiles clearly depleted. The antiradical capacity, measured by DPPH*, was well correlated with phytochemical amounts, also showing the same decreasing trend in 2011. This behavior can be depended on the different climate conditions in the two years, particularly in the period August-September of 2011. Besides, the plant stress was evidenced in 2011 also by a significantly decreased productivity.